2022
DOI: 10.1039/d1na00835h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient charge transfer from organometal lead halide perovskite nanocrystals to free base meso-tetraphenylporphyrins

Abstract: We reported the efficient charge transfer studies from methylammonium lead halide, MAPbX3 (X = Br, I), perovskite nanocrystals (PNCs) to 5,10,15,20-tetraphenylporphyrin (TPP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…[18][19][20][21] Recently, we reported the use of PNCs in charge transfer to meso-tetraphenylporphyrin. 22 Despite this, the actual potency of PNCs to utilize their electronic and optical properties remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Recently, we reported the use of PNCs in charge transfer to meso-tetraphenylporphyrin. 22 Despite this, the actual potency of PNCs to utilize their electronic and optical properties remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…identified the charge transfer of perovskite with mesoporous titanium dioxide. Previous studies explored the charge transfer phenomenon from electron donor perovskites to acceptor groups such as fullerenes, carbon nanotubes, perylenes, RhB, benzoquinone, TiO 2 , and porphyrins . For example, Wu et al revealed the timescale of ultrafast electron transfer from perovskites to phenothiazine and benzoquinone.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies explored the charge transfer phenomenon from electron donor perovskites to acceptor groups such as fullerenes, 36 carbon nanotubes, 37 perylenes, 38 RhB, 39 benzoquinone, 40 TiO 2 , 41 and porphyrins. 42 For example, Wu et al 40 revealed the timescale of ultrafast electron transfer from perovskites to phenothiazine and benzoquinone. Subsequently, Long et al 43 reported the ultrafast interfacial charge transfer from PNCs to TiO 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…2 Their high power conversion efficiency (PCE), high photoluminescence quantum yields (PLQY), narrow emission bands, and tunability of band gaps by size, shape, dimensionality, and composition make them ideal aspirants for optoelectronic devices, e.g., solar cells, LEDs, lasers, specific photodetectors, and visible-light communication. [3][4][5][6][7][8][9][10][11] Nonetheless, the main weakness of lead halide perovskite is the poor chemical stability under ambient conditions. These are very sensitive in the presence of moisture, air, light, and temperature due to their low formation energy.…”
Section: Introductionmentioning
confidence: 99%
“…, solar cells, LEDs, lasers, specific photodetectors, and visible-light communication. 3–11 Nonetheless, the main weakness of lead halide perovskite is the poor chemical stability under ambient conditions. These are very sensitive in the presence of moisture, air, light, and temperature due to their low formation energy.…”
Section: Introductionmentioning
confidence: 99%